Influence of organic sources of nutrients on vanilla (Vanilla planifolia) as an intercrop in coconut garden - V. Krishnakumar, H. P. Maheswarappa,; A. Geetha Kumari, Alka Gupta, (Journal of Plantation Crops, 2016)
Performance of vanilla, as influenced by organic source of nutrition when grown as intercrop in coconut garden, was studied in sandy loam soil at ICAR-CPCRI, Kasaragod, Kerala for seven years. Field experiments were carried out with different sources of organic manures, recommended NPK fertilizer and no fertilizer treatments. Application of cow dung slurry (6 tonnes ha-1) resulted in vigorous growth of vine (vine length of 5.5 m) and higher number of beans per vine (208) and a significantly higher mean fresh yield of bean (1.87 kg vine-1). Application of vermicompost (5 kg plant-1) + biofertilizers (Bacillus and Azospirillum) and vermiwash were on par and recorded mean fresh yield of 1.47 kg vine-1 and 1.30 kg vine-1, respectively. Control treatment without fertilizer application recorded significantly lower fresh bean yield (0.55 kg vine-1) due to lower number of beans per vine (72 nos.).Â In the rhizosphere of vanilla, no significant difference for either bacterial or actinomycetes population was noticed among the treatments. The fungal population differed significantly among the treatments and the highest population level was found with application of biogas slurry (62.1x103cfu g-1 soil), which was on par with application of cow dung slurry (59x103 cfu g-1 soil). Among the function specific microbial communities, the highest population ofÂ P-solubilisers (98x103 cfu g-1 soil) was recorded in the biogas slurry treatment, and it was the lowest in control and vermiwash application treatments. The average coconut yield realized during experimental period(2004-05 to 2009-10) was 136 nuts per palm, recording 53 per cent increase in yield compared to pre-experimental yield (89 nuts per palm).Â